1998
DOI: 10.1002/(sici)1521-4141(199810)28:10<3321::aid-immu3321>3.0.co;2-m
|View full text |Cite
|
Sign up to set email alerts
|

Genetic linkage analysis of collagen-induced arthritis in the mouse

Abstract: The genetic susceptibility to collagen-induced arthritis (CIA) in mice, the most commonly used model for rheumatoid arthritis, has been analyzed. The highly susceptible B10.RIII strain was crossed with the resistant RIIIS/J strain and the F2 intercross mice were subjected to genomic screening using microsatellite markers. These strains share the MHC region on chromosome 17, known to be of importance in CIA (this locus is named Mcia1). The same cross has earlier been used to map the major genes outside the MHC … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
59
2

Year Published

2000
2000
2005
2005

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 82 publications
(61 citation statements)
references
References 29 publications
0
59
2
Order By: Relevance
“…Amd1 and Asm1 may be a common locus for the same etiology of these 2 kinds of diseases. This is also the first study to map a gene locus for susceptibility to spontaneous arthropathy in DBA/1 mice, Amd2, on chromosome 3 in the region of a DBA/1 (14,22) and other mouse and rat models (23)(24)(25). However, the region of Amd2 did not share any of the loci involving the MHC.…”
Section: Discussionmentioning
confidence: 86%
“…Amd1 and Asm1 may be a common locus for the same etiology of these 2 kinds of diseases. This is also the first study to map a gene locus for susceptibility to spontaneous arthropathy in DBA/1 mice, Amd2, on chromosome 3 in the region of a DBA/1 (14,22) and other mouse and rat models (23)(24)(25). However, the region of Amd2 did not share any of the loci involving the MHC.…”
Section: Discussionmentioning
confidence: 86%
“…We have found the original Cia5/Eae3 locus 13,14 to consist of three loci affecting separate phases of the progression of arthritis, which each interacted uniquely with loci on chromosome 15. Cia5 affects disease onset and early severity, whereas Cia21 and Cia22 affect the chronic/late phase of the disease.…”
Section: Discussionmentioning
confidence: 99%
“…Since we previously observed that genotypes homozygous for the short GA 13 and GA 16 alleles or heterozygous GA 13 /GA 16 were associated to MS, we specifically examined these three genotypes in JRA patients. As can be seen from Figure 2, all the three genotypes were increased among the JRA patients, but only the heterozygous GA [13][14][15][16] genotype reached statistical significance (5% vs 1%; OR ¼ 3.9; 95% CI (1.4-11.6); P n ¼ 4 ¼ 0.036). Overall, JRA patients carried significantly more frequent two copies of 'short' alleles (GA 13 and/or GA 16 ) compared to healthy controls (10% vs 6%; OR ¼ 1.9; 95% CI (1.1-3.5); P n ¼ 2 ¼ 0.04).…”
mentioning
confidence: 86%